Analysis of Student Science Process Skills in The Practicum of Physical Chemistry Based on Linguistic and Interpersonal Intelligence - Asmorowati, Dian Sri; Wardani, Sri; Mahatmanti, F. Widhi (International Journal of Active Learning, 2021)
This study aims to determine the level of mastery of science process skills in physicsÃ‚Â Ã‚Â Ã‚Â chemistry practicum students based on linguistic and interpersonal intelligence. This research was conducted with a quantitative descriptive method. This research was conducted with a quantitative descriptive method. The respondents of this study were 66 students of the 2017 class of chemistry study program consisting of two classes. The data collection technique is done by interview, observation, documentation, and test. This research was conducted in the physical chemistry laboratory of the Department of Chemistry, Universitas Negeri Semarang. The research results obtained were the percentage of science process skills of students of the 2017 batch of chemistry study program students. The result of the percentage of science process skills in class 1 students is an indicator of formulating hypothesis with a percentage 74.26%, interpreting data 73.53%, and asking questionÃ‚Â 77.57%. The result of the percentage of science process skills in class 2 students is an indicator of formulating hypothesis with a percentage 71,88%, interpreting data 74.22%, and asking questionÃ‚Â 72.27 %.